What hampers research collaboration in a~region? - Tobias Johannes Hertrich; Thomas Brenner (Review of Regional Research, 2024)
Abstract Research collaboration is an important instrument for innovation and knowledge transfer. In this respect, barriers that prevent or impede research collaboration between research institutions and companies are of particular importance. In this paper, we elaborate on the importance of research collaboration barriers by conducting and analysing 77~expert interviews from ten German regions. We go beyond the existing literature by examining differences in the perception of different kinds of experts and by comparing different types of regions classified according to the presence of important actors, namely research institutions and large companies. Our results show that research collaboration barriers are perceived as very significant barriers to innovation across all region types. We find differences in the perception of research collaboration barriers between the experts. On the regional level, the presence of research institutions shifts the relevance from missing partners to other research collaboration barriers, while all research collaboration barriers are not perceived as significantly less important.
Additional information: O3;R1;I2
Keywords: 330; RIS; Barriers to research collaboration; UI collaboration